Reuse of orthopedic implants in a peri-implant fracture of both forearm bones in an adolescent: A case report - Aguilar-Chavez, Felipe; Jorba-Elguero, Pedro; Cruz-Cortés, Mónica Alejandra; González-González, Fernando (Journal of Musculoskeletal Surgery and Research)
Fractures of both forearm bones in adolescents are common. Many of these fractures are surgically fixed with internal fixation. However, among the complications that can occur are peri-implant fractures, which are somewhat infrequent. They are due mainly to high-energy injuries. Therefore, not much information about them is found in the literature. Reusing implants is not a frequent or well-documented practice, and it is carried out only when the necessary resources are unavailable, particularly in developing countries. We are reporting a 16-year-old male patient who suffered a peri-implant fracture distal to plates that were placed 3 years earlier in both left forearm bones. The material was removed successfully and reused, achieving an adequate reduction and fixation with one dynamic compression plate (DCP) plate for the radius and one reconstruction plate for the ulna. The patient recovered successfully. This case report aimed to understand the lack of resources in a developing country and a possible solution for this problem in this type of scenario.